Activity of Fluorine-Containing Analogues of WC-9 and Structurally Related Analogues against Two Intracellular Parasites: Trypanosoma cruzi and Toxoplasma gondii - Chao, Maria Noelia (2016)
Two obligate intracellular parasites, Trypanosoma cruzi, the agent of Chagas disease, and Toxoplasma gondii, an agent of toxoplasmosis, upregulate the mevalonate pathway of their host cells upon infection, which suggests that this host pathway could be a potential drug target. In this work, a number of compounds structurally related to WC-9 (4-phenoxyphenoxyethyl thiocyanate), a known squalene synthase inhibitor, were designed, synthesized, and evaluated for their effect on T. cruzi and T. gondii growth in tissue culture cells. Two fluorine-containing derivatives, the 3-(3-fluorophenoxy)- and 3-(4-fluorophenoxy)phenoxyethyl thiocyanates, exhibited half-maximal effective concentration (EC50) values of 1.6 and 4.9 μm, respectively, against tachyzoites of T. gondii, whereas they showed similar potency to WC-9 against intracellular T. cruzi (EC50values of 5.4 and 5.7 μm, respectively). In addition, 2-[3- (phenoxy)phenoxyethylthio]ethyl-1,1-bisphosphonate, which is a hybrid inhibitor containing 3-phenoxyphenoxy and bisphosphonate groups, has activity against T. gondii proliferation at sub-micromolar levels (EC50=0.7 μm), which suggests a combined inhibitory effect of the two functional groups.